Law Under The Grip Of Power - Hutauruk, Appe (CV. Publikasi Indonesia, 2025)
The concept of the state of law is an idea that is considered the most ideal applied today in the context of a welfare state, although the concept is carried out with different perceptions and methods in each country in the world. The term